Peran Pendidikan Dalam Meningkatkan Kesadaran Ekonomi Syari’ah - Yulia Febriyati (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Education is a learning process both through formal and informal activities whose aim is none other than individual self-development. As an effort to master various aspects, both cognitive, affective and psychomotor. Sharia economics in the current modernization context, especially in the concept of the Indonesian state, does not only focus on Muslims. Indonesia's multicultural society with various cultures, languages and religions is a very important market in the development of sharia economics. Likewise in educational institutions. This research was conducted with the aim of observing the extent of the role of education in increasing Sharia Economic Awareness. The research methods used are observation and interviews. Observing and distributing questionnaires to be filled out by STAI Nurul Falah Airmolek students, especially the Sharia Economics Study Program and several other study program students.The results of this research show that students have a strong interest in sharia economics. They realize the importance of the understanding of Sharia Economics that they obtain to convey to society. However, it is a challenge for students because there are still many students who are not yet literate or aware of the presence of Sharia Banking. Social life and the environment are one of the factors that they consider that they don't really need banking services. Even though times have changed digitally. However, this is the reality that is happening today in the regional environment and is an effort for educators, practitioners and Sharia Banking itself to more aggressively build the interest of the academic community and academics in Sharia Banking.